EFFORTS TO PREVENT THE NEGATIVE IMPACT OF GADGET USE ON ADOLESCENTS IN CILILIN - Siti Nuralifah; Maulana Yusup; Iyan Herviana (JLER (Journal of Language Education Research), 2021)
Gadget addiction is a problem that needs attention from the wider community. Of course this has a negative impact on adolescents, the most visible of which is the negative impact on health, psychological impact, social impact and academic impact. This research is expected to help in the prevention of gadget addiction. The purpose of this research is to study and describe various ways to prevent gadget addiction. The method used in this research is descriptive qualitative method. The population in this study were adolescents in the city of Cililin with a sample of four adolescents. The research was conducted for one week. The data collection techniques used were observation and interviews. The results of this study indicate that 1) gadgets make teenagers rarely communicate directly with friends and even their surroundings, communication is done through social media 2) gadgets make teenagers addicted to playing them, the reason these teenagers play gadgets is because there is a certain satisfaction when playing these gadgets